Effect of Body Surface Area on Severe Osteoporotic Fractures: A Study of Osteoporosis in Changsha China - Wu, Xi-Yu; Li, Hong-Li; Shen, Yi; Tan, Li-Hua; Yuan, Ling-Qing; Dai, Ru-Chun; Zhang, Hong; Peng, Yi-Qun; Xie, Zhong-Jian; Sheng, Zhi-Feng (Frontiers in Endocrinology, 2022)
Clinical vertebral fractures and femoral neck fractures are severe osteoporotic fractures that increase morbidity and mortality. Anthropometric variables are associated with an increased risk of osteoporotic fractures, but it is not clear whether body surface area (BSA) has an effect on clinically severe osteoporotic fractures. The study included total of 3,694 cases of clinical vertebral fractures and femoral neck fractures (2,670 females and 1,024 males) and 3,694 controls without fractures who were matched with the cases by sex and age. There was a significant positive correlation between BSA and bone mineral density (BMD) in female and male fracture patients (females: r = 0.430–0.471, P < 0.001; males: r = 0.338–0.414, P < 0.001). There was a significant systematic increase in BMD in both genders at various skeletal sites, grouped by BSA quartile. The osteoporosis rates of the lumbar spine (97.9%), femoral neck (92.4%) and total hip (87.1%) in the female Q1 group were significantly higher than those in the Q4 group (P < 0.001), which were 80.0%, 57.9% and 36.9%, respectively, in the Q4 group; the osteoporosis rates of the lumbar spine, femoral neck, and total hip were 53.9%, 59.4%, and 36.3% in the male Q1 group, and 15.2%, 21.9%, and 7.03% in the Q4 group, which were significantly lower than those in the Q1 group (P < 0.001). In age-adjusted Cox regression models, the risk of fracture in the remaining three groups (Q2, Q3, and Q4) for weight, BMI, and BSA for both genders, compared with the highest quartile (Q1 by descending quartile stratification) were significantly higher. In models adjusted for age and BMD, only men in the BSA Q3 (HR = 1.55, 95% CI = 1.09–2.19) and BSA Q4 groups (HR = 1.41, 95% CI = 1.05–1.87) had significantly higher fracture risks. In models adjusted for age, height, weight, BMI, and BSA, low BMD was the greatest fracture risks for both sexes. Our results show that BSA is closely related to BMD, prevalence of osteoporosis, and fracture risk, and that a decline in BSA may be a new potential risk factor for osteoporotic fractures in Chinese men.